Аналіз конкурентоспроможності організаційно-економічних систем будівельних підприємств за допомогою виробничих функцій - Юрковський, Р. Ф. (Ways to Improve Construction Efficiency, 2012)
Methodological approach to the analysis of the competitive structure of the industry and methods of study ways to improve the competitiveness and investment attractiveness of the construction companies.